2021
DOI: 10.1101/2021.06.03.21258241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multisystemic cellular tropism of SARS-CoV-2 in autopsies of COVID-19 patients

Abstract: Background: Multiorgan tropism of SARS-CoV-2 has previously been shown for several major organs. Methods: We have comprehensively analyzed 25 different formalin-fixed paraffin-embedded (FFPE) tissues/organs from autopsies of fatal COVID-19 cases (n=8), using detailed histopathological assessment, detection of SARS-CoV-2 RNA using polymerase chain reaction and RNA in situ hybridization, viral protein using immunohistochemistry, and virus particles using transmission electron microscopy. Finally, we confirmed t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Histopathological examination of adrenal glands obtained from autopsies revealed a high degree of local inflammation. While in some studies an inconspicuous 25 or sporadic focal inflammation 26 was found, other observations report a more pronounced and frequent infiltration of CD3- and CD8-lymphocytes in different layers of the adrenal cortex 27 or lymphoplasmacellular cells in perivascular regions of the adrenal gland 28 . Furthermore, one study reported a cellular hyperplasia in zona fasciculata of the adrenal cortex in 86% of investigated patients, which might be an indicator of impaired hormone production 29 .…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Histopathological examination of adrenal glands obtained from autopsies revealed a high degree of local inflammation. While in some studies an inconspicuous 25 or sporadic focal inflammation 26 was found, other observations report a more pronounced and frequent infiltration of CD3- and CD8-lymphocytes in different layers of the adrenal cortex 27 or lymphoplasmacellular cells in perivascular regions of the adrenal gland 28 . Furthermore, one study reported a cellular hyperplasia in zona fasciculata of the adrenal cortex in 86% of investigated patients, which might be an indicator of impaired hormone production 29 .…”
Section: Introductionmentioning
confidence: 92%
“…However, vascular damage seems to be the most commonly confirmed complication of COVID-19 in adrenal glands. In particular, a high degree of endotheliitis of periadrenal adipose and parenchymal tissues was found 25 28 , along with acute fibroid necrosis and apoptotic debris of adrenal arteriole 30 . Moreover, histological 31 and routine computer tomography (CT) investigations 26 32 reported thrombi formation, infarctions, and hemorrhages in the adrenal glands of patients with COVID-19 33 34 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation